Trouble du spectre de l’autisme et études postsecondaires : points de vue d'intervenants des services d'aide aux étudiants - Valérie Michaud; Georgette Goupil (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The number of students with Autism Spectrum Disorder (ASD) enrolling in postsecondary education, in college and university, is rising (AQICESH, 2019-2020). However, the ASD characteristics create challenges, for these students, and new interventions for the support services to students with disabilities. The purpose of this qualitative study is to collect the reported services members’ experiences in Quebec postsecondary institutions regarding the students' strengths and challlenges associated with ASD. It also aims to describe the services members' experiences concerning the perceived support need by professors and other actors in college or university. Fourteen support services members, divided into six focus group, were interviewed in colleges and universities. The results of the thematic analysis reveal the complexity of support demands that can be associated with ASD. The analysis of the strengths and challenges of students with ASD helps to identify intervention targets as well as the importance given to mental health aspects. The results also highlight the need of formation on ASD in postecondary establishments.